2008
DOI: 10.1016/j.technovation.2008.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding novelty creation in exploration networks—Structural and relational embeddedness jointly considered

Abstract: In exploration networks the key-organisational question is not how to organise a division of labour but instead how to create novelty. The aim of this paper is to develop an understanding of how such novelty in exploration networks is created. Based on an empirical analysis of the multimedia and biotechnology industries in the Netherlands, this paper shows that exploration networks face a trade-off between diversity and selection. Moreover, the findings indicate that depending on the type of exploration task, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 46 publications
(68 reference statements)
2
82
0
4
Order By: Relevance
“…Dado que se desea estudiar la red en el contexto de la difusión de información y conocimiento, la cantidad de tiempo se aproximó con la frecuencia en que el individuo se enriquece con información, sugerencias o estímulos que sus contactos realizan en la red (se utilizó una escala de Likert de 5 puntos). Inspirado en el trabajo de Gilsing (2008), los servicios recíprocos se aproximan con el alcance de los contenidos y se indaga sobre los temas que el individuo se informa a través de la red. La Tabla 8 describe el resto de las características relacionales evaluadas.…”
Section: Características Relacionalesunclassified
“…Dado que se desea estudiar la red en el contexto de la difusión de información y conocimiento, la cantidad de tiempo se aproximó con la frecuencia en que el individuo se enriquece con información, sugerencias o estímulos que sus contactos realizan en la red (se utilizó una escala de Likert de 5 puntos). Inspirado en el trabajo de Gilsing (2008), los servicios recíprocos se aproximan con el alcance de los contenidos y se indaga sobre los temas que el individuo se informa a través de la red. La Tabla 8 describe el resto de las características relacionales evaluadas.…”
Section: Características Relacionalesunclassified
“…actors) and structure (i.e. relationships) varies with the resource that is being accessed (Gilsing and Duysters, 2008;Sousa et al, 2011) and with the sector where firms operate (Plum and Hassink, 2011). It has namely shown that the type of relationships established by new technology-intensive firms will be largely determined by the nature of the knowledge being exploited and by the mode of industrial organisation of the sector/industry where the resulting technologies products are being introduced .…”
Section: The Role Of Network In Technology-based Entrepreneurshipmentioning
confidence: 99%
“…On the one hand, learning takes place where there are differences in knowledge. On the other hand, too large cognitive distance makes basic mutual understanding unachievable (Gilsing and Duysters, 2008). Many studies have found that though difference in knowledge base of innovation partners is a crucial condition leading to interorganizational innovation (Nelson and Winter, 1982), it also has a negative effect on absorptive capacity because it creates learning problems resulting from the lack of basic mutual understanding between each other.…”
Section: Technological Distancementioning
confidence: 99%